SURVIVAL OF BACTERIA EXPOSED TO EXTREME ACCELERATION: IMPLICATIONS FOR PANSPERMIA - Mastrapa R.M.E.; Glanzberg H.; Head J.N.; Melosh H.J.; Nicholson W.L. (My University, 2001)
We studied the effect of extreme acceleration and change in acceleration, or jerk, on bacteria to determine if they could survive impact ejection from a planet. Computer simulations based on the spallation model [H.J. Melosh, Icarus 59 (1984) 234-260; H.J. Melosh, Nature 363 (1993) 498-499] for ejecting material from planetary surfaces provided estimates for acceleration, rise time, and jerk for material accelerated to escape velocity. For ejection from Mars, the maximum acceleration predicted was 3x106 m/s2, or 3x105xg, with a rise time of 0.5 ms, and a corresponding jerk of 6x109 m/s3. We tested the resistance of Bacillus subtilis spores and Deinococcus radiodurans cells to high acceleration and jerk by (1) subjecting B. subtilis spores to the forces of an ultracentrifuge and (2) firing both bacteria from a rifle into a plasticene target. We measured the survival of B. subtilis spores at extreme acceleration in an ultracentrifuge operated at its highest speed, 100#000 rpm, corresponding to an acceleration of 4.27x106 m/s2, or 4.36x105xg. Approximately 107 spores were centrifuged in phosphate-buffered saline for 24, 48, 50 and 72 h. Spores were inactivated with simple exponential kinetics, and 65 h of centrifugation was required to inactivate 90% of the spore population. To test for resistance to jerk, spores of B. subtilis or cells of D. radiodurans were loaded into the rear cavities of lead pellets fired from a compressed-air pellet rifle into a target consisting of plasticene modeling clay, previously chilled to 4°C. The velocity of each pellet was measured using a chronograph and the depth of penetration of each pellet into the target was measured before removing the pellet from the clay using sterile forceps. Two different rifles were used, one with a measured pellet velocity of ~100 m/s and the other with a velocity of ~300 m/s. These correspond to estimated accelerations of 1.5x106 and 4.5x106 m/s2 and jerks of 1.5x1010 and 1.5x1011 m/s3, respectively. The percent survival for both organisms ranged from 40 to 100%. The samples in the ballistic experiments were subjected to jerks and accelerations 2.5-25 times larger than those estimated to prevail during ejection according to the computer simulation. We therefore conclude that acceleration and jerk are not important lethal factors during the ejection of viable microorganisms from planetary surfaces.
Keywords: BACTERIA; EXOBIOLOGY; INTERPLANETARY SPACE; MARTIAN METEORITES; IMPACT CRATERS; SIMULATION